A economia onto-teológica no pensamento do jovem Heidegger - Queiroz, Luismar Cardoso de (2018)
In our research, we will try to thematize, analyze and re-think from the thinking of the young Heidegger a specific mobility of thought that moves within the scope of the selfunderstanding circularity of being-there, and which, for this reason, moves within the historicity of factual life. We will present this mobility of thought in the concept of ontotheological economy: a dynamic of thought which, as we shall see, develops in the early period of Heidegger's philosophy, but retains its intensity and force of determination in all paths of thought which later open to this philosopher. The onto-theological economy is realized in the commutative meditation of the modal contents (formal clues) that permeate the living stream of the religious facticity of Christianity; liberating, from its movement, phenomenological insights that open access to the original dimension of time and being.